Masowa prywatyzacja w Polsce jako jeden z elementów budowania społeczeństwa obywatelskiego - Patkowski, Krzysztof (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Privatization was and has remained one of the most important elements of the transformations that have taken place in all countries with a centralized economy. Alexander Solzhenitsyn observed that “it is impossible to create a state governed by laws without first having an independent citizen ... But there can be no independent citizen without private property”. Consequently, it is the rapid privatization that directly influences the process of building civic society in post-communist countries. Krzysztof Murawski claims that the reason for that is that there is a direct relationship between freedom and property. Property is closely related to freedom as it provides citizens with the feeling of independence from the state and allows them to gather the results of their work as renewable goods that can be freely managed and multiplied for one’s own individual as well as the social good. It can be assumed that the development of private property produces two advantageous social results: the efficiency of business activity increases as does the realm of responsible political freedom.